2011
DOI: 10.1523/jneurosci.3885-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Scene Content from Spatial Boundary: Complementary Roles for the Parahippocampal Place Area and Lateral Occipital Complex in Representing Real-World Scenes

Abstract: Behavioral and computational studies suggest that visual scene analysis rapidly produces a rich description of both the objects and the spatial layout of surfaces in a scene. However, there is still a large gap in our understanding of how the human brain accomplishes these diverse functions of scene understanding. Here we probe the nature of real-world scene representations using multivoxel functional magnetic resonance imaging pattern analysis. We show that natural scenes are analyzed in a distributed and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
227
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(262 citation statements)
references
References 46 publications
(58 reference statements)
34
227
1
Order By: Relevance
“…In humans, neuroimaging and neuropsychological work suggests that place recognition is primarily mediated by the parahippocampal place area (PPA), a region of medial occipitotemporal cortex that responds strongly when subjects view environmental scenes or landmark objects (21-23), whereas heading retrieval is primarily mediated by a system centered around the retrosplenial complex (RSC) in the medial parietal lobe (24)(25)(26)(27)(28). Analogous to the current findings, the PPA appears to be sensitive to both geometric and nongeometric information (22,(29)(30)(31)(32)(33), whereas RSC appears to be especially sensitive to geometry when people retrieve spatial information from memory (28). In rodents, the homologous regions are postrhinal cortex (34), which has been shown to be important for place recognition (35), and retrosplenial cortex, which has been shown to be important for deriving directional information from environmental cues (36).…”
Section: Discussionsupporting
confidence: 74%
“…In humans, neuroimaging and neuropsychological work suggests that place recognition is primarily mediated by the parahippocampal place area (PPA), a region of medial occipitotemporal cortex that responds strongly when subjects view environmental scenes or landmark objects (21-23), whereas heading retrieval is primarily mediated by a system centered around the retrosplenial complex (RSC) in the medial parietal lobe (24)(25)(26)(27)(28). Analogous to the current findings, the PPA appears to be sensitive to both geometric and nongeometric information (22,(29)(30)(31)(32)(33), whereas RSC appears to be especially sensitive to geometry when people retrieve spatial information from memory (28). In rodents, the homologous regions are postrhinal cortex (34), which has been shown to be important for place recognition (35), and retrosplenial cortex, which has been shown to be important for deriving directional information from environmental cues (36).…”
Section: Discussionsupporting
confidence: 74%
“…Overall, posterior PHG appears to have a more general role in scene processing, possibly reflecting a viewpoint‐independent processing of scene structure [Epstein et al, 2007; Epstein and Higgins, 2007] that is insensitive to scene familiarity [Epstein et al, 1999; Epstein, 2008] and the position of a scene within its broader environment [Epstein et al, 2003; Epstein, 2005; Park and Chun, 2009]. This conclusion is supported by evidence that posterior PHG is sensitive to spatial boundary [Park et al, 2011], rectilinearity [Nasr et al, 2014], and motion within visual scenes [Korkmaz Hacialihafiz and Bartels, 2015]. PHG also shows a greater response to scenes with low, compared with high, feature overlap [Mundy et al, 2012].…”
Section: Discussionmentioning
confidence: 98%
“…To investigate, we operationalized spatial layout as scene size, that is the size of the space a scene subtends in the real-world (Kravitz et al, 2011a;Park et al, 2011Park et al, , 2015. Using multivariate pattern classification (Carlson et al, 2013;Cichy et al, 2014;Isik et al, 2014) and representational similarity analysis (Kriegeskorte, 2008;Kriegeskorte and Kievit, 2013;Cichy et al, 2014) on millisecond-resolved magnetoencephalography data (MEG), we identified a marker of scene size around 250 ms, preceded by and distinct from an early signal for lower-level visual analysis of scene images at ~100ms.…”
Section: The Temporal Dynamics Of Spatial Layout Processingmentioning
confidence: 99%
“…individual scenes and navigation-related processing. Although the cortical loci of spatial layout perception in humans have been well described (Aguirre et al, 1998;Kravitz et al, 2011b;MacEvoy and Epstein, 2011;Mullally and Maguire, 2011;Park et al, 2011;Bonnici et al, 2012), the dynamics of spatial cognition remain unexplained, partly because neuronal markers indexing spatial layout processing remain unknown, and partly because quantitative models of spatial layout processing are missing. The central questions of this study are thus twofold: First, what are the temporal dynamics with which representation of spatial layout emerge in the brain?…”
Section: Introductionmentioning
confidence: 99%